Bibliographie zu Flavius Josephus : Supplementband mit Gesamtregister - Schreckenberg, Heinz. (Arbeiten zur Literatur und Geschichte des hellenistischen Judentums, 1979)
After being cast out of the Clan that had adopted her as a child by the new leader, Ayla shares a lonely valley with a herd of steppe ponies, harnesses their power, and discovers speech and love with Jondalar, a member of her own race.